A Qualitative Systematic Review of Facilitators of and Barriers to Community Pharmacists–Led Anticoagulation Management Service. Issue 6 (June 2022) - Egunsola, Oluwaseun; Li, Joyce W.; Mastikhina, Liza; Akeju, Oluwasefunmi; Dowsett, Laura E.; Clement, Fiona
Objective: To identify the facilitators of and barriers to the implementation of Community Pharmacists–Led Anticoagulation Management Services (CPAMS). Data Sources: MEDLINE, EMBASE, CINAHL, Cochrane Database of Systematic Reviews, and Cochrane CENTRAL Register of Controlled Trials were searched from inception until August 20, 2021. Study Selection and Data Extraction: All abstracts proceeded to full-text review, which was completed by 2 reviewers. Data extraction was completed by a single reviewer and verified. Analysis was completed using best-fit framework synthesis. Data Synthesis: A total of 17 articles reporting on CPAMS from 6 jurisdictions were included: 2 Canadian provincial programs (Nova Scotia, Alberta), a national program (New Zealand), and 3 cities in the United Kingdom (Whittington and Brighton and Hove) and Australia (Sydney). Facilitators of CPAMS included convenience for patients, accessibility for patients, professional satisfaction for pharmacists, increased efficiency in anticoagulation management, improved outcomes, enhanced collaboration, and scalability. Barriers included perceived poor quality of care by patients, resistance by general practitioners, organizational limits, capping of the number of eligible patients, and cost. Relevance to Patient Care and Clinical Practice: The barriers and facilitators identified in this review will inform health policy makers on the implementation and improvement of CPAMS for patients and health care practitioners. Conclusion and Relevance: CPAMS has been implemented in 6 jurisdictions across 4 countries, with reported benefits and challenges. The programs were structurally similar in most jurisdictions, with minor variations in implementation. New anticoagulation management programs should consider adapting existing frameworks to local needs.